2022
DOI: 10.3389/feduc.2022.751548
|View full text |Cite
|
Sign up to set email alerts
|

The Next Black Box of Formative Assessment: A Model of the Internal Mechanisms of Feedback Processing

Abstract: In this theoretical paper, we shift the attention from feedback as something given to feedback as something received. After Black and Wiliam shined a light into the black box of the classroom and identified formative assessment as a way to raise standards of achievement, a large body of research revealed the influence of feedback on learning. Not all such influences were positive, however, which created a need for closer examinations of the nature of feedback. In addition, recent scholarship on assessment as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 101 publications
(180 reference statements)
1
12
0
Order By: Relevance
“…From these results, we can conclude that students have a very positive attitude towards the teacher and the class. This result is also in accordance with the results of previous studies which showed a significant difference in the use of formative tests in favour of the experimental group (Van der Kleij et al, 2018;Ismail & Tini, 2020;Lui & Andrade, 2022;Voinea, 2018;Evans et al, 2014;Dayal, 2021;Gezer et al, 2021;Alsubaiai, 2021).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…From these results, we can conclude that students have a very positive attitude towards the teacher and the class. This result is also in accordance with the results of previous studies which showed a significant difference in the use of formative tests in favour of the experimental group (Van der Kleij et al, 2018;Ismail & Tini, 2020;Lui & Andrade, 2022;Voinea, 2018;Evans et al, 2014;Dayal, 2021;Gezer et al, 2021;Alsubaiai, 2021).…”
Section: Resultssupporting
confidence: 93%
“…There are many studies on the application of formative assessment at different levels of education, where the results of these studies explain the increase in student academic achievement because of the application of formative assessment (Van der Kleij et al, 2018;Ismail & Tini, 2020;Lui & Andrade, 2022;Voinea, 2018;Evans et al, 2014;Wylie & Ciafalo, 2010). In this study, the observations made by the researcher also support the results in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, the implementation of formative assessment in teachers’ daily practice remains a substantial challenge because teachers often adopt only a few of the principles associated with formative assessment (goal setting, gathering data about students’ learning, giving feedback to students). Moreover, they do not fully integrate it into their teaching approach ( Hunt and Pellegrino, 2002 ; Bennett, 2011 ; Wylie and Lyon, 2015 ; Heitink et al, 2016 ; Yan and Brown, 2021 ; Yan et al, 2021 ; Lui and Andrade, 2022 ). Exploring the antecedents and conditions of formative assessment practices are thus of prime importance when seeking to better understand which personal and contextual factors enable and maximize the use of formative assessment in the classroom ( Heitink et al, 2016 ; Schildkamp et al, 2020 ; Yan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an early yet seminal work, Kluger and DeNisi [ 7 ] argued that the response to and action taken on feedback were more significant than the types of feedback received. In a similar vein, Lui and Andrade [ 8 ] asserted that the connotation of feedback has shifted from “giving” information to “receiving” information. Specifically, Liu and Andrade [ 8 ] disintegrated the internal process of feedback into a four-step procedure: 1) initial motivation; 2) elicitation; 3) interpretation of feedback and 4) decision-making based on feedback.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Lui and Andrade [ 8 ] asserted that the connotation of feedback has shifted from “giving” information to “receiving” information. Specifically, Liu and Andrade [ 8 ] disintegrated the internal process of feedback into a four-step procedure: 1) initial motivation; 2) elicitation; 3) interpretation of feedback and 4) decision-making based on feedback. Scholars also emphasized “feedback culture”, with which students would be encouraged to participate in feedback to improve learning outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%